PENGARUH LOYALITAS DAN DISIPLIN TERHADAP PRODUKTIFITAS INSTITUSI - WAHYU, WAHYU; IBDALSYAH, IBDALSYAH; AYUNIYYAH, QURROH (Universitas Ibn Khaldun Bogor, 2021)
This study examines the factors that affect employee productivity in companies and institutions or institutions. The purpose of this study is to analyze: First, the effect of amyl loyalty on the productivity of institutions on Laznas-BMH. Second, The influence of amyl discipline on institutional productivity in Laznas-BMH. Third. The influence of loyalty and discipline on institutional productivity on Laznas-BMH. To sharpen the analysis of the problems discussed in this study, the author explains the meaning of Zakat, Productivity, loyalty, and discipline according to the review of several experts. The discussion of the Baitul Maal Hidayatullah National Amil Zakat Institute (Laznas-BMH) describes the history of its establishment, BMH, and the programs that have been carried out so far and the development of BMH from its establishment to the present. The data was collected from the library of researt and observation in the field and used a questionnaire with a total of 100 respondents. The data contained will then be analyzed with descriptive analysis and quantitative analysis. The variables in this study consisted of two free variables, namely loyalty (X1), discipline (X2). The results of this study are first, there is a sinifikan influence between the loyalty of amyl BMH (X1) on the productivity of amyl zakat BMH (Y) with a ttable value of 1.985 and a count of 7.327 meaning thitung 7.325 > of 1.985 with a significance of 0.000<0.025. Secondly, there is a significant influence between the discipline of amyl BMH (X2) on the productivity of amyl BMH (Y) with a ttabel value of 1.985 and a counting value of 2.424, meaning a count of 2.424 > of 1.985 with significance 0.002<0.025. Third, there is a significant influence between the loyalty of amyl BMH (X1) and the discipline of amyl BMH (X2) on the productivity of amyl BMH (Y) with a calculated value of 101.280. Meaning that the calculated value is 101.280>ftabel 2.70 with a significance level of 0.000<0.05.